USING WEBLOGS IN ESP CLASSROOM - Jano, Zanariah (Journal of Human Capital Development (JHCD), 2008)
Journal Writing on the web, or so called weblogs has become the most popular medium of communication among the youth. Hence, it is essential to ascertain how these weblogs can be implemented in the classroom environment and study the students’ perception towards the approach. This study is action based in nature whereby the researcher has implemented the weblogs in the classroom. A Content analysis was conducted to analyze the students’ blogs. A questionnaire was given to each student and several interview sessions were conducted to explore the students’ perception of this blogging phenomenon. The findings revealed that weblogs act as an intermediary tool to improve literacy level through online communication and an access to experience creative and free expression through writing. Moreover, it is also noted that weblogs allow students to engage actively in writing and improve motivation for learning without much pressure and anxiety. The application of weblogs in English language learning environments facilitates, encourages and creates a conducive environment for the students’ acquisition of language. Keywords: weblogs, ESP classrooms, perceptions, reflections, content analysis, virtual